Strategy to Strengthen Legal Certainty in Determining BPHTB to Support Development in North Sumatra - Meta Permata Sari; Surya Perdana Ginting; Farid Wajdi (Law Development Journal, 2026)
Land and Building Acquisition Tax (BPHTB) is a source of Regional Original Income that plays a strategic role in supporting regional fiscal independence. However, in practice, the determination of BPHTB in several districts/cities in North Sumatra Province still faces various problems that impact on weak legal certainty for taxpayers. These problems include differences in the assessment of the Taxable Object Acquisition Value (NPOP), regulatory fragmentation between regions, limited apparatus capacity, and the lack of integration of tax and land administration information systems. This study aims to analyze weaknesses in the determination of BPHTB and formulate strategies to strengthen legal certainty to support regional development in North Sumatra. This study uses a normative legal research method with a statutory, conceptual, and limited empirical approach through an analysis of BPHTB administrative policies and practices in the region. Data were obtained through a literature review of relevant laws and regulations, policy documents, and scientific literature, then analyzed qualitatively. The research results indicate that the weak legal certainty in determining the Land and Building Tax (BPHTB) is caused by the lack of standardization of the NPOP assessment methodology, disparities in administrative procedures between regions, limited capacity of regional tax officials, and the lack of integration of information systems between institutions involved in land administration and taxation. To overcome these problems, a strategy is needed to strengthen legal certainty through standardization of taxable object assessment methodology, digitization and integration of the BPHTB administration system, strengthening the objection mechanism, and increasing the capacity of regional tax officials. With effective and transparent policy implementation, the BPHTB determination system is expected to provide legal certainty for taxpayers while enhancing the role of BPHTB as a supporting instrument for sustainable regional development in North Sumatra Province.